ELECTRICALLY HEATED HANDWEAR - Madnick, Herman; Park, Alice (1967)
Electrically heated handwear is presented as a solution to the hand- protection problem for equipment operators and other military personnel who must use their hands in extremely cold conditions for prolonged periods. The problem of hand cold injury, the inadequacy of conventional solutions and existing handwear, and various experimental approaches are discussed. The U.S. Army Natick Laboratories has assembled an auxiliary electrical handwear system and is continuing research efforts to improve electrically heated handwear. It is concluded that because of the demonstrated need for such handwear and the current feasibility of manufacturing it, electrically heated handwear should be supplied to the appropriate personnel.